Mechanism and optimization of enhanced electro-kinetic remediation on 137Cs contaminated kaolin soils: A semi-pilot study based on experimental and modeling methodology. (10th September 2018) - Mao, Xinyu; Shao, Xiaohou; Zhang, Zhanyu; Han, Fengxiang
Abstract: Csium-137 ( 137 Cs) contamination resulted from wastes disposal and incidents holds serious threat to ecosystems and human health. Electro-kinetic remediation (EKR) is a promising technique for the 137 Cs remediation while soil pH polarization remains to be the obstacle for improving its performance. In this study, strategies of non-uniform electric intensity (EI) and polarity reversal (PR) have been employed to enhance the EKR. A 2-dimensinal (2D) numerical model was applied to stimulate the transport-reactive processes and predict the possible electro-chemical variations during the remediation. Within 168 h treatment, each strategy could increased the EKR efficiency on 137 Cs removal by 5% and larger increase (12%) was observed when combined these two strategies. Good agreements were achieved between the experimental and model results which further verified the feasibility of enhanced EKR on soil 137 Cs removal. In addition, a polynomial linear fitting analysis was implemented for the optimization of PR frequency. The 24 h was determined as the optimal PR frequency and 90% of 137 Cs (276 mg) in polluted kaolin was eliminated within 415 h by PR-EKR under a non-uniform EI. Moreover, the energy utilization efficiency and cost for such technology was obtained in an acceptable value of 0.96 mg/kWh and 829, respectively. The results of the semi-pilot experiments indicated that EKR enhanced with non-uniform EI and PR strategies might be practicable and effective for the decontamination of soil 137 Cs in full-scale applications. Highlights: Polarity reversal integrated with non-uniform potential improved the performance of EKR on soil 137 Cs decontamination. A 2D numerical model illuminated the transport-reactive processes and validated the reinforcements of enhanced EKR. A Linear fitting analysis based on a polynomial model determined the optimal polarity reversal frequency. A specific energy utilization efficiency analysis verified the feasibility of enhanced EKR in pilot-scale applications.